2014
DOI: 10.1155/2014/494581
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of PR, ER, NF-κB, and TNF-αin Breast Cancer

Abstract: Objectives. To investigate the expression of estrogen (ER), progesterone receptors (PR), nuclear factor-κB (NF-κB), and tumor necrosis factor-α (TNF-α) in human breast cancer (BC), and the correlation of these four parameters with clinicopathological features of BC. Methods and Results. We performed an immunohistochemical SABC method for the identification of ER, PR, NF-κB, and TNF-α expression in 112 patients with primary BC. The total positive expression rate of ER, PR, NF-κB, and TNF-α was 67%, 76%, 84%, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 30 publications
3
31
0
Order By: Relevance
“…Both ER and PR status correlated significantly with the stage of the disease, thereby indicating that ER, PR positive tumors were associated with early stage breast tumors. Similar correlation was also found in other studies (Zhou et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Both ER and PR status correlated significantly with the stage of the disease, thereby indicating that ER, PR positive tumors were associated with early stage breast tumors. Similar correlation was also found in other studies (Zhou et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Following the assessment of the role of NF-κB expression in breast tumor samples, one study showed that the frequency of p65 expression is higher in tumor cells of HER2 and basal-like subtypes compared to its expression in luminal A subtype cancer cells [58]. Another study, however, reported an association between ER and NF-κB expression, where the NF-κB expression correlates with higher tumor grade, stage III-IV, and lymph node metastasis [59]. Furthermore, Oida et al reported that NF-κB participated in the tamoxifen resistance in breast cancer cell line [60].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we analyzed the impacts of TME-driven stimuli on the responses of CCR7-expressing luminal-A breast tumor cells to CCL21 chemotactic gradients in vitro and in vivo. The TME stimulus was induced by simultaneous exposure of luminal-A breast tumor cells to representatives of 3 relevant arms of the TME: 1) estrogen, the key hormonal factor in luminal-A tumors, which by definition, all express ER [18,19]; 2) TNF-a, a representative of the inflammatory arm; this cytokine has direct tumor-promoting effects in breast cancer and is expressed by ;90% of breast cancer patients with recurrent disease, including ER+ breast tumors [39][40][41][42][43]; and 3) EGF, a growth-stimulating factor that prevails in breast tumors [44,45]. Luminal-A tumors express EGFR and are characterized by high levels of ErbB3 [46][47][48].…”
Section: Introductionmentioning
confidence: 99%